Scyliorhinus hachijoensis, a new species of catshark from the Izu Islands, Japan (Carcharhiniformes: Scyliorhinidae) - Ito, Nanami; Fujii, Miho; Nohara, Kenji; Tanaka, Sho (Zootaxa, 2022)
A new species of catshark genus Scyliorhinus, S. hachijoensis sp. nov., is described for the islands of Mikurajima, Hachijojima, and Torishima in southeastern Japan. Scyliorhinus hachijoensis has clasper hooks, which is a common feature in males of the most closely related species (S. torazame), but is distinguished by its coloration (presence of dark spots), the height of its anal fin (higher than the caudal peduncle), and the shape of pectoral and pelvic fins, and dermal denticles. Molecular data also corroborates the new species as a distinct and monophyletic taxon by nucleotide sequence analysis of three mitochondrial DNA regions.